2022
DOI: 10.1007/s10493-022-00747-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological abnormalities in Hyalomma dromedarii and Hyalomma rufipes (Acari: Ixodidae) collected from dromedary camels (Camelus dromedarius) in Aswan, Egypt

Abstract: The present study reports anomalies in Hyalomma dromedarii and Hyalomma rufipes adults collected from dromedary camels (Camelus dromedarius) in Aswan, Egypt, between January and June 2022. A total of 52 adult ticks displayed one or several local and/or general anomalies. A wide variety of local anomalies was observed including atrophy of one or multiple legs, ectromely, absence of accessory adanal and subanal plates, fusion of adanal and accessory plates, and presence of sclerotized formation in the ventral pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Though this is the first report of local anomalies in A. lepidum from Egypt, a previous study from Uganda (Balinandi et al 2019 ) has reported local and general anomalies for the same species. Morphological abnormalities and anomalies in Hyalomma dromedarii and H. rufipes in ticks from Egypt have previously been observed in the country (Okely et al 2022a ). The observation of anomalous ticks in Egypt in this study and the previous one (Okely et al 2022a ) may be due to antiparasitic treatments used in Egypt.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Though this is the first report of local anomalies in A. lepidum from Egypt, a previous study from Uganda (Balinandi et al 2019 ) has reported local and general anomalies for the same species. Morphological abnormalities and anomalies in Hyalomma dromedarii and H. rufipes in ticks from Egypt have previously been observed in the country (Okely et al 2022a ). The observation of anomalous ticks in Egypt in this study and the previous one (Okely et al 2022a ) may be due to antiparasitic treatments used in Egypt.…”
Section: Discussionmentioning
confidence: 77%
“…Morphological abnormalities and anomalies in Hyalomma dromedarii and H. rufipes in ticks from Egypt have previously been observed in the country (Okely et al 2022a ). The observation of anomalous ticks in Egypt in this study and the previous one (Okely et al 2022a ) may be due to antiparasitic treatments used in Egypt. Mutations resulting from antiparasitic treatments such as insecticides and acaricides that hard ticks are exposed to may give rise to morphologically anomalous ticks (Luz et al 2023 ).…”
Section: Discussionmentioning
confidence: 77%